The disappearing product marketing and markets in the creative industries - Bilton, Chris (Edward Elgar Publishing, 2017)
Technological and social change has transfigured the market for creative industries. A new generation of intermediaries including Amazon, Apple, Facebook and Google deal in context (how we consume) more than content (what we consume), displacing cultural producers, devaluing culturing products and monopolising consumer attention. Drawing on theoretical models across disciplines and rich in practical examples, this book charts an approach to marketing which challenges cultural producers to reclaim their place in the creative economy. / Verlag